(untitled) (Nóema, 2020)
Whitehead is a mathematician who gives full powers to feeling. The speculative cosmology that he elaborates in Process and Reality is a transcendental aesthetic in which feeling is elevated to the real condition of every experience. Not, therefore, a transcendental aesthetic in the Kantian sense. The philosophy of the organism aims to reverse the process by which Kant derives the world from the subject, and ’feeling’ is exactly the name of the process by which the subject emerges from the object. Kant was close to discovering this when he introduced sensation as the door of perception. And yet, its unpredictability - synonymous with variability, subjectivity and aposteriority - forces him to leave it out of transcendental analysis. Whitehead, on the contrary, by redefining the status of subjectivity in terms of feeling, recovers it, and the aim of this article is to show how he succeeds in this venture, that is, how he moves from the cause as category, to feeling as cause.